An examination of the initial cancer consultation of medical and radiation oncologists using the Cancode interaction analysis system - Dimoska, A (Nature Publishing Group, 2008)
This study provides an analysis of the structure of the initial cancer consultation, the consultation styles of medical and radiation oncologists, and their effect on patient outcomes. One hundred and fifty-five cancer patients attending their first consultation with either a medical or radiation oncologist were audiotaped and the transcripts were analysed using the Cancode computer interaction analysis system. Findings revealed that medical oncologists allowed patients and their families more input into the consultation and were rated as warmer and more patient-centred compared with radiation oncologists. However, radiation oncologists spent a longer period discussing, and were more likely to bring up, social support issues with patients. Both medical and radiation oncologists varied their consultation style according to the patient's gender, age, anxiety levels, prognosis, and education. Patients seeing an oncologist who was rated as warmer and discussed a greater number of psychosocial issues had better psychological adjustment and reduced anxiety after consultation. These findings provide current evidence that may be used to inform improvements of communication skills training for oncologists and highlight the need for future communication research to separately consider oncologists from different disciplines.